Web Information Systems and Model in E-Retailing-A REVIEW - Raqeyah Jawad Najy (IJRDO -Journal of Computer Science Engineering, 2020)
We present in this research several patterns that can be used to improve Web Information System with search capabilities. We first introduce and justify the need for adding search functionality to Web applications; next we briefly explain the context in which we discovered these patterns. Finally, Web-search patterns are presented illustrating them with examples of successful information systems in the Internet. Successful Web-based information systems (WIS) are critical for electronic retailers to attract and retain consumers and deliver business functions and strategy. However, the design and development of a WIS may include many business, technology and user challenges. Understanding and fulfilling the critical requirements of these challenges will determine the success of a WIS commercial application. In this research, we present an abstract model for WIS design in e-retailing. this model offers an integrated and overall view, where four interconnected layers are investigated: business determinants; WIS; business interface; and users/customers. Through our discussion of this model, we provide researchers with a better understanding of WIS issues requiring further investigation, and provide practitioners with a foundation to understand WIS requirement s and features for success.